Accuracy of commercially available c-reactive protein rapid tests in the context of undifferentiated fevers in rural Laos. Issue 1 (December 2015) - Phommasone, Koukeo; Althaus, Thomas; Souvanthong, Phonesavanh; Phakhounthong, Khansoudaphone; Soyvienvong, Laxoy; Malapheth, Phatthaphone; Mayxay, Mayfong; Pavlicek, Rebecca; Paris, Daniel; Dance, David; Newton, Paul; Lubell, Yoel
Abstract Background C-Reactive Protein (CRP) has been shown to be an accurate biomarker for discriminating bacterial from viral infections in febrile patients in Southeast Asia. Here we investigate the accuracy of existing rapid qualitative and semi-quantitative tests as compared with a quantitative reference test to assess their potential for use in remote tropical settings. Methods Blood samples were obtained from consecutive patients recruited to a prospective fever study at three sites in rural Laos. At each site, one of three rapid qualitative or semi-quantitative tests was performed, as well as a corresponding quantitative NycoCard Reader II as a reference test. We estimate the sensitivity and specificity of the three tests against a threshold of 10 mg/L and kappa values for the agreement of the two semi-quantitative tests with the results of the reference test. Results All three tests showed high sensitivity, specificity and kappa values as compared with the NycoCard Reader II. With a threshold of 10 mg/L the sensitivity of the tests ranged from 87–98 % and the specificity from 91–98 %. The weighted kappa values for the semi-quantitative tests were 0.7 and 0.8. Conclusion The use of CRP rapid tests could offer an inexpensive and effective approach to improve the targeting of antibiotics in remote settings where health facilities are basic and laboratories are absent. This study demonstrates that accurate CRP rapid tests are commercially available; evaluations of their clinical impact and cost-effectiveness at point of care is warranted.